Unions, training and firm performance - John T. Addison; Clive R. Belfield (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
This paper uses data from two British workplace surveys to examine the impact of unions on several training measures. It also evaluates the impact of unions and training on earnings and two measures of firm performance. Union effects on training emerge as fairly subtle, and are more positive when using individual rather than plant-wide training data. A positive impact of training on earnings is detected in individual and plant-wide wage data, albeit for one of the datasets. Union influence on wages is also muted and union-training interaction effects vary greatly. However, instrumenting training provides positive results for labour productivity and, again for one survey, for financial performance as well.
Keywords: 330; betriebliche Weiterbildung; Gewerkschaftspolitik - Auswirkungen; Lohnhöhe; Unternehmenserfolg; Großbritannien